An Experience on Deciding National Projects and Developments - Carelli, Francesco (British Journal of Healthcare and Medical Research, 2023)
As EURACT member International Expert, I was invited in WHO Committee. The aim was to support a Ministry of Health abroad in developing the post - graduate curricula in Family Medicine and a real development for Family Medicine ( FM ). Method. It took more than three seasons to formalise a real change. After home works, also analysing materials received from abroad, and online meetings, five full days were spent in that country, meeting Health Ministry, Medical Teachers, three National Medical Associations, two Regional Health Authorities, Primary Health Centres ( PHCs ) in different cities and contexts. The experience was repeated, at 3 months distance, at Ministry in the capital for full two days with National Starring Group, WHO team, EU Projects representative, all National Associations and Academicians involved, Health Minister again.